Quality of life domains revised by people with multiple sclerosis and healthcare professionals for adaptive measure development - Ambra Mara Giovannetti; Andrea Giordano; Edoardo Donarelli; Giulia Di Domenico; Giampaolo Brichetto; Eleonora Cocco; Francesco Patti; Rachele Paolucci; Alessandra Solari; Silvia Testa; Rosalba Rosato (PLoS ONE, 2026)
Background Multiple sclerosis (MS) significantly affects individuals’ health-related quality of life (HRQoL). Ideally, HRQoL assessment tools for MS should be patient-centered, ensuring that each item meaningfully contributes to measurement precision. The present study has three main objectives: (1) a review of the literature to identify key HRQoL domains by examining existing instruments; (2) confirmation and integration of HRQoL domains based on stakeholders’ input; (3) systematic comparison of the categories and subcategories identified by the stakeholders with the domains identified in the literature review. Methods Findings from the literature review were discussed in four focus group meetings (FGMs) with key stakeholders, including people with MS (PwMS) and healthcare professionals (HPs). Participants were purposively sampled to ensure diversity in geographic location, gender, education, and (for PwMS) disease severity. FGMs were audio-recorded, transcribed verbatim, and analyzed using qualitative content analysis by two independent researchers. The categories and subcategories generated from the qualitative analysis were then systematically compared with the items of the MS-specific HRQoL instruments identified in the literature review, by two independent researchers. Results Out of 5190 references, 308 records related to 9 instruments were included in the literature review. The main HRQoL domains were then extracted and discussed with the steering committee, and informed the FGM grids. The results validated the HRQoL domains identified in literature and provided deeper insights into their complexity. Conclusion This study confirmed and added granularity to the existing HRQoL domains relevant to PwMS, identifying key areas for inclusion in future research. The findings contribute to the development of a more comprehensive, patient-centered HRQoL assessment tool, which could inform targeted interventions to enhance quality of life in PwMS.